AGAMA SEBAGAI MODALITY DALAM MELAKUKAN TERAPEUTIK JIWA - Sabari (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2019)
The purpose of this study is to describe religion which can be a modality in providing a therapeutic effect on one's soul. The result of this research is that religion as modality is a communication process in doing therapeutics to the soul. Religion is seen as a therapy in overcoming mental problems. The existence of a practiced religion is a form of spiritual surrender which ultimately affects mental health and has an effect on physical health. This significant relationship becomes the foundation of strength for every soul that religion will affect every line of life.